Reduced-graphene-oxide-reinforced boron carbide ceramics fabricated by spark plasma sintering from powder mixtures obtained by heterogeneous co-precipitation. Issue 13 (September 2019) - Li, Ming; Wang, Weimin; He, Qianglong; Wang, Aiyang; Hu, Lanxin; Fu, Zhengyi
Abstract: Reduced graphene oxide (rGO) sheets were uniformly dispersed in boron carbide ceramics by a heterogeneous co-precipitation method. This approach was used to improve the fracture toughness of boron carbide ceramics and to address the problem of agglomeration of graphene in the boron carbide matrix. Cetyltrimethyl ammonium bromide was used as a heterogeneous co-precipitation reaction initiator to prepare a homogeneously dispersed graphene oxide/boron carbide (GO/B4 C) mixture. Reduced graphene oxide/boron carbide (rGO/B4 C) powder mixtures with good dispersion were obtained by high temperature heat treatment. Dense rGO/B4 C composite ceramics were fabricated by spark plasma sintering at 1800 °C and 50 MPa. The fracture toughness and flexural strength of the rGO/B4 C with an rGO content of 2 vol% composite increased by 42% (from 3.43 to 4.88 MPa·m 1/2 ) and 28% (from 372 to 476 MPa) compared with those of pure B4 C, respectively. The markedly improved fracture toughness and flexural strength of the boron carbide ceramics were attributed to the effect of crack bridging and crack deflection by graphene sheets, graphene interface sliding, and pulling out of graphene.